A Water‐Splitting Carbon Nitride Photoelectrochemical Cell with Efficient Charge Separation and Remarkably Low Onset Potential. Issue 48 (8th November 2018) - Peng, Guiming; Albero, Josep; Garcia, Hermenegildo; Shalom, Menny
Abstract: A simple method to grow a closely packed carbon nitride (CN) film by the crystallization of CN monomers on a conductive substrate followed by a thermal condensation is reported. The as‐synthesized CN exhibits excellent performance as photoanode material in a photoelectrochemical cell. Detailed (photo)electrochemical and transient absorption measurements indicate excellent charge separation properties, high hole‐extraction efficiency (up to 50 %), a long electron lifetime, and low amount of defect states below the CN conduction band. Consequently, the CN photoanode exhibits a markedly low overpotential of 0.25 V versus reversible hydrogen electrode (RHE), which is comparable with the state‐of‐the‐art metal‐based photoanodes, an impressive photocurrent density of 116 μA cm −2 at 1.23 V versus RHE in an alkaline solution without sacrificial agent, as well as excellent stability over a wide pH range (0–13). Abstract : A simple and straightforward method is shown to grow a closely packed and porous CN layer directly on a conductive substrate as a photoanode, and it has excellent photoelectrochemical activity. The CN photoanode exhibits an exceptionally low onset potential, a high photocurrent density, an external quantum efficiency of 8.5 % at 400 nm, and good stability over a wide pH range.